Effect of Blood Flow Restriction on Tissue Oxygenation during Knee Extension. Issue 1 (January 2015) - Ganesan, Goutham; Cotter, Joshua A.; Reuland, Warren; Cerussi, Albert E.; Tromberg, Bruce J.; Galassetti, Pietro
ABSTRACT: Purpose: Time-resolved near-infrared spectroscopy was used to quantify tissue oxy- and deoxyhemoglobin concentrations ([HbO2 ] and [HbR]) and O2 saturation (stO2 ) in the oblique fibers of the vastus medialis muscle and brain prefrontal cortex during knee extension with and without blood flow restriction (BFR). Methods: Six young healthy males performed three sets of knee extensions on a dynamometer (50% one-repetition maximum) separated by 90-s rest periods in three conditions: 1) until fatigue without BFR (fatigue), 2) until fatigue with BFR (100 mm Hg cuff constriction around thigh (BFR)), 3) same number of repetitions from condition 2 without BFR (matched). Each condition was performed on a separate visit. Results: BFR was associated with higher [HbR] at the oblique fibers of the vastus medialis muscle (rest 1: 57.8 (BFR) vs 35.0 μM (matched); P < 0.0001) and a significantly lower stO2 during recovery periods between sets (7.5%–11.2 % lower than non-BFR conditions for rest 1 and 2, P < 0.0001). Using a piecewise linear spline method, a spike in [HbR] was observed before the onset of HbR clearance during recovery, causing HbR clearance to begin at a higher concentration (81 (BFR) vs 62 μM (matched), P = 0.029). [HbO2 ] kinetics during recovery were also affected by BFR, with longer duration (BFR, 51 s; matched, 31 s; P = 0.047) but lower rate of increase (BFR, 58 μM·min −1 ; matched, 89 μM·min −1 ; P = 0.004) during recovery. In the prefrontal cortex, BFR was associated with increased [HbR], diminished increase in [HbO2 ], and higher subjective exertion. Conclusions: These findings yield insight into possible physiological mechanisms of BFR and suggest a role of time-resolved near-infrared spectroscopy in monitoring and optimization of BFR exercise on an individual basis.